SHOULD GENDER AND SEXUALITY STUDIES BE INCLUDED IN LANGUAGE EDUCATION? - Ferraz, Daniel Mello (Trama, 2016)
<pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">One of the great challenges faced by foreign language <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">education in Brazil is to deal with the multiplicity of philosophies, <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">theories, and practices. The National Curricular Orientations <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">suggest that we connect linguistic pedagogical practices with <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">sociocultural and critical ones. Thus, this work investigates gender <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">and sexuality studies (LOURO, 1997) in the perspectives of <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">undergrad language students of a Brazilian Federal University. <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">The methodology is qualitative, and the action research method <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">was applied. Hence, based on data collected from a discipline of <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">academic writing, we discuss how students address such themes, <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">specially homosexuality and homophobia (BORRILO, 2010). <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">We also discuss if these themes should be included or excluded <pre style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial">from language classes.